New data on Marthiella Buffington (Hymenoptera, Cynipoidea, Figitidae), with description of a new species - Gallardo, Fabiana Edith (2014)
New data on Marthiella Buffington (Hymenoptera, Cynipoidea, Figitidae), with description of a new species. A new species of Marthiella Buffington (Hymenoptera, Figitidae) from Brazil and Nicaragua is described and illustrated. Rhabdeucoela semirufa Kieffer is transferred to Marthiella and a new combination was established: Marthiella semirufa. A key for identifying species of Marthiella is provided in this study.